2019
DOI: 10.1111/jeb.13489
|View full text |Cite
|
Sign up to set email alerts
|

Tail colour signals performance in blue tit nestlings

Abstract: Indirect sexual selection arises when reproductive individuals choose their mates based on heritable ornaments that are genetically correlated to fitness. Evidence for genetic associations between ornamental colouration and fitness remains scarce. In this study, we investigate the quantitative genetic relationship between different aspects of tail structural colouration (brightness, hue and UV chroma) and performance (cell‐mediated immunity, body mass and wing length) in blue tit (Cyanistes caeruleus) nestling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…However, males raised in reduced broods developed feathers with higher UV chroma. This sex-specific effect was hypothesised to be the result of early-acting sexual selection, as tail feathers are not replaced during post-juvenile moult, and this was hypothesised to play a signalling role in mate choice during the first breeding season (Jacot and Kemepenaers, 2007;Class et al, 2019;Badás et al, 2020). Interestingly, in a brood size manipulation experiment on eastern bluebirds (Sialia sialis), structurally coloured wing feathers were also shown to be brighter in male nestlings from reduced broods, compared with those from enlarged broods, whereas no analogous effect was found in females (Siefferman and Hill, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, males raised in reduced broods developed feathers with higher UV chroma. This sex-specific effect was hypothesised to be the result of early-acting sexual selection, as tail feathers are not replaced during post-juvenile moult, and this was hypothesised to play a signalling role in mate choice during the first breeding season (Jacot and Kemepenaers, 2007;Class et al, 2019;Badás et al, 2020). Interestingly, in a brood size manipulation experiment on eastern bluebirds (Sialia sialis), structurally coloured wing feathers were also shown to be brighter in male nestlings from reduced broods, compared with those from enlarged broods, whereas no analogous effect was found in females (Siefferman and Hill, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Both breast and tail colouration of blue tit nestlings were shown to be condition dependent in correlational (Johnsen et al, 2003) and experimental (Jacot and Kempenaers, 2007) studies, but only the latter study showed a sex-specific effect on rectrices structural colouration. A recent quantitative genetics study, besides finding low heritability of tail structural colouration, surprisingly showed that, at a genetic level, UV chroma of rectrices is negatively related to the proxies of a bird's performance: body mass, wing length and cell-mediated immunity (Class et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our findings show that there were among‐nest effects of nestling body mass on total brightness. Unlike UV chroma, it is less likely that brightness functions as a signal of genetic quality, since it shows low heritability (e.g., see Charmantier et al, 2017 for blue tit adults and Class et al, 2019 for nestlings). However, it may reflect parental quality effects or other (common) environmental effects (e.g., food stress or parasite infection, see above).…”
Section: Discussionmentioning
confidence: 99%
“…These traits have often been explained as by‐products of selection acting on colouration in adults, at least when both offspring and adults display the same traits (similar to female ornaments, which, initially, were only interpreted as correlated effects of selection in males; see discussion by Amundsen, 2000 ; see also Doutrelant et al, 2020 ; West‐Eberhard, 1983 ). However, given the low‐heritability estimates of certain colorations (Charmantier et al, 2017 ; Class et al, 2019 ; Drobniak et al, 2013 ), offspring coloration may have important signaling functions in itself like signaling quality or need to parents. For example, the occurrence of natal coats in primates—distinct from adult fur—seems to have evolved to solicit greater maternal care (Higley et al, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of conspicuous coloration has been the focus of many studies, particularly in birds. Many of these studies demonstrate how indicator models of sexual selection, and in particular female choice, have driven the evolution of colorful plumage in males because of the relationship between color and individual color components (intensity, hue, and chroma) and measures of individual male quality (e.g., Class et al 2019;Bruinjé et al 2019;Lui et al 2018). Little emphasis has been placed on studies that show a lack of female preferences based on intraspecific color signals, despite their condition dependence.…”
Section: Choicesmentioning
confidence: 99%